Permselectivity coefficient of anion exchange membranes for electrodialysis of citric acid - Sarmidi, Mohamad Roji; Md Yunos, Khairul Faezah; Ling, Lay Pee (Faculty of Chemical and Natural Resources Engineering, UTM, 2001)
The anion exchange membrane find application in diverse process such as electrodialysis, diffusion analysis, membrane electrolysis, reverse osmosis and membrane fuel cells, which are energy, resource and environment saving. The development of ion-exchange membrane of high chemical, mechanical and thermal stability, which meet growing demand of the aforementioned processes, is of great importance. This paper deals with the determination of the membrane permselectivity coefficient of anion exchange membranes for concentration of citric acid using electrodialysis process. The permselectivity coefficient of three types of commercial anion exchange membranes; Neosepta ACS(Tokuyama, Japan), Neosepta AHA2(Tokuyama, Japan) and 204UZR412(Ionics. Inc., USA) were compared in consideration to the physicochemical data of these membranes published so far are not adequate to their industrial application particularly for citric acid concentration. The permselectivity coefficient is the ability of anion exchange membrane to allow a selective passage of citrate ions (Cit3-) and chloride ions (Cl-) under the influence of electrical potential difference. To measure the permselectivity coefficient of different types of anion exchange membrane, the experimental conditions were maintained at a constant value. The initial concentration of feed solution was maintained at 0.1M sodium citrate and 0.1M of sodium chloride. The constant current density used was 432 A/m2 and the flow rate was 500 ml/min.